Identification of immunoreactive secretory proteins from the stationary phase culture of Burkholderia pseudomallei - Vellasamy, K.M.; Mariappan, V.; Hashim, Onn Haji; Vadivelu, J. (2011)
Bacterial secreted proteins are known to be involved in virulence and may mediate important host-pathogen interactions. In this study, when the stationary phase culture supernatant of Burkholderia pseudomallei was subjected to 2-DE, 113 protein spots were detected. Fifty-four of the secreted proteins, which included metabolic enzymes, transcription/translation regulators, potential virulence factors, chaperones, transport regulators, and hypothetical proteins, were identified using MS and database search. Twelve of these proteins were apparently reactive to antisera of mice that were immunised with B. pseudomallei secreted proteins. These proteins might be excellent candidates to be used as diagnostic markers or putative candidate vaccines against B. pseudomallei infections.